ANTI DUMPING DUTY AS A MEASURE OF CONTINGENT PROTECTION : AN ANALYSIS OF INDIAN EXPERIENCE - Nandana Baruah (Centre for Development Studies-WP377, 2005)
The aim of this paper is to analyse India's anti dumping behaviour. India has become a major user of anti dumping measures, initiating more than 300 cases against many of its trading partners. After looking at the trends and patterns in the use of anti dumping measures by India, the paper tries to identify the various factors that influence the anti dumping procedure in India at different stages. The study finds that, many of the allegedly dumped products have experienced substantial increase in their imports into India. Again, many domestic producers seeking protection are performing unsatisfactorily. However, when it comes to the final decision by the authority to impose anti dumping duty, none of these factors appear to be significantly influencing that decision. Rather a less concentrated industry tends to get more anti dumping protection. The paper concludes with the observation that the anti dumping actions in India cannot be justified on predatory ground. However, the author feels that strategic actions on the part of the stake-holders should be explored to better understand the anti dumping behaviour of the nation.